2018
DOI: 10.1126/scitranslmed.aau4711
|View full text |Cite
|
Sign up to set email alerts
|

Anti-α4β7 therapy targets lymphoid aggregates in the gastrointestinal tract of HIV-1–infected individuals

Abstract: Gut homing CD4+ T cells expressing the integrin α4β7 are early viral targets and contribute to HIV-1 pathogenesis, likely by seeding the gastrointestinal (GI) tract with HIV. Although simianized anti-α4β7 monoclonal antibodies have shown promise in preventing or attenuating the disease course of simian immunodeficiency virus in nonhuman primate studies, the mechanisms of drug action remain elusive. We present a cohort of individuals with mild inflammatory bowel disease and concomitant HIV-1 infection receiving… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 66 publications
6
42
0
Order By: Relevance
“…Moreover, immune aggregates may be retained efficiently in the mucus by binding of the Fc domain of IgG to mucins and specific binding in the vaginal tract to MUC16 (164). Analogous mechanisms may act on other mucosal surfaces, such as those in the gastrointestinal tract (165).…”
Section: Antibody Capture Of Infectious Hiv Particles/aggregationmentioning
confidence: 99%
“…Moreover, immune aggregates may be retained efficiently in the mucus by binding of the Fc domain of IgG to mucins and specific binding in the vaginal tract to MUC16 (164). Analogous mechanisms may act on other mucosal surfaces, such as those in the gastrointestinal tract (165).…”
Section: Antibody Capture Of Infectious Hiv Particles/aggregationmentioning
confidence: 99%
“…The direct link between α4β7 expression and the viral reservoir is supported by recent findings by Uzzan et al It was recently showed that administering the Food and Drug Administration (FDA)-approved drug Vedolizumab that masks α4β7 expression in leukocytes reduces the size of lymphoid aggregates in the terminal ileum of HIV infected individuals [61]. Lymphoid aggregates have been suggested as key foci in which the latent reservoir is maintained within the gut.…”
Section: Discussionmentioning
confidence: 90%
“…Why we observe a significant enrichment of naïve B cells in vedolizumab endoscopic remitters cannot be fully answered based on our findings, and raises the question whether a vedolizumab induced depletion of this cell population is key to its therapeutic success. Indeed, recent data on a small cohort of HIVinfected IBD patients demonstrated that vedolizumab therapy importantly reduced naïve B cells in intestinal mucosa, 29 preventing subsequent priming by dendritic cells, who are surveying the mucosal barrier for invading pathogens.…”
Section: Discussionmentioning
confidence: 99%